2019
DOI: 10.1088/1748-9326/ab5256
|View full text |Cite
|
Sign up to set email alerts
|

Limiting global warming to 1.5 °C will lower increases in inequalities of four hazard indicators of climate change

Abstract: Clarifying characteristics of hazards and risks of climate change at 2°C and 1.5°C global warming is important for understanding the implications of the Paris Agreement. We perform and analyze large ensembles of 2°C and 1.5°C warming simulations. In the 2°C runs, we find substantial increases in extreme hot days, heavy rainfalls, high streamflow and labor capacity reduction related to heat stress. For example, about half of the world's population is projected to experience a present day 1-in-10 year hot day ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…We also estimate the 10 %-90 % confidence intervals of the fitting curves by applying a 1000-time random sampling of the observed data: we randomly resample 20-year samples from the original 20-year (1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016) data and compute a and b; we repeat the random resampling process 1000 times; we consider that the 10th percentile and 90th percentile values of the 1000 regression lines indicate the 10 %-90 % confidence intervals. These non-linear relationships are consistent with previous studies (Lestari et al, 2014;Spessa, et al, 2015;Yin et al, 2016;Field et al, 2016). We use the relationships in Fig.…”
Section: Empirical Functionssupporting
confidence: 87%
See 1 more Smart Citation
“…We also estimate the 10 %-90 % confidence intervals of the fitting curves by applying a 1000-time random sampling of the observed data: we randomly resample 20-year samples from the original 20-year (1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016) data and compute a and b; we repeat the random resampling process 1000 times; we consider that the 10th percentile and 90th percentile values of the 1000 regression lines indicate the 10 %-90 % confidence intervals. These non-linear relationships are consistent with previous studies (Lestari et al, 2014;Spessa, et al, 2015;Yin et al, 2016;Field et al, 2016). We use the relationships in Fig.…”
Section: Empirical Functionssupporting
confidence: 87%
“…S1). Previous studies found that fire activity and related emissions have non-linear relationships with precipitation anomalies and accumulated water deficits (Lestari et al, 2014;Spessa, et al, 2015;Yin et al, 2016;Field et al, 2016). Figure 2 shows the empirical relationships between the EA-averaged precipitation anomalies (GPCP) and the EA cumulative burned area and fire CO 2 and PM 2.5 emissions (GFED4s) between 1997 and 2016.…”
Section: Empirical Functionsmentioning
confidence: 97%
“…In line with findings showing that no HSI can be identified to be superior than others for quantifying epidemiological impacts (e.g., Barnett et al., 2010; Burkart et al., 2011; Heo & Bell, 2018; Kim et al., 2011; Ragettli et al., 2017; Vaneckova et al., 2011), results of the present study do not allow for recommendations on the usage of any particular HSI – except that our results confirm the findings of Lemke and Kjellstrom (2012) that the usage of T WBGs should be avoided. Trends in TX X , which is a widely used heat indicator in climate science (e.g., Shiogama et al., 2019; Sillmann et al., 2013), are in line with trends in the other HSIs. As recent findings even question the importance of humidity as contributing factor to higher mortality (Armstrong et al., 2019), TX X , a comparatively simple indicator, might indeed provide reliable estimates of future heat stress trends.…”
Section: Discussionmentioning
confidence: 69%
“…TX is often used as a simple heat indicator in climate science (e.g., Fischer & Schär, 2010; Sillmann et al., 2013; Shiogama et al., 2019). Several epidemiological studies apply TX in addition to daily mean temperature to estimate heat‐related mortality or morbidity (e.g., Barnett et al., 2010; Heo & Bell, 2018; Zhang et al., 2014).…”
Section: Methods and Datamentioning
confidence: 99%
“…Lee et al (2018) indicated that warming by more than half a degree brings more intense and more frequent precipitation events to the Asian monsoon region. Shiogama et al (2019) suggested that regions with relatively large increases of extreme hot days, heavy rainfall, high streamflow and labor capacity reductions related to heat stress coincide with those countries that are characterized by low CO 2 emissions, low income, and high vulnerability. Limiting global warming to 1.5 K, compared to 2 K, lowers these inequalities.…”
Section: Introductionmentioning
confidence: 99%